Analisis Pengaruh Literasi Ekonomi, Iklan, Kontrol Diri Dan Fomo Terhadap Pembelian Impulsif Pada Gen Z - Anggraini, Tika Septi; Hak, Nurul; Yustati, Herlina (JPSDa: Jurnal Perbankan Syariah Darussalam, 2025)
This study aims to analyze the effect of economic literacy, advertising, self-control, and Fear of Missing Out (FOMO) on impulse buying in Generation Z in Bengkulu City. The research method used is quantitative with the Partial Least Square (PLS) approach with the SmartPLS 4 application, involving 86 Generation Z respondents aged 12-27 years in Bengkulu City who were selected through probability sampling techniques. The variables analyzed include economic literacy, advertising, self-control, and FOMO as independent variables, and impulse buying as the dependent variable. The results showed that economic literacy (t-statistic = 1.548; p-value = 0.122), advertising (t-statistic = 1.764; p-value = 0.078), and self-control (t-statistic = 1.897; p-value = 0.059) had no significant influence on impulse buying. This shows that although respondents have a good level of economic literacy, their consumption behavior is still influenced by emotional impulses. In contrast, FOMO has a significant positive influence (t-statistic = 3.872; p-value = 0.000), indicating that social pressure and the desire not to fall behind trends are the main drivers of impulse buying in Generation Z. From an Islamic perspective, this impulsive behavior contradicts the principles of consumption taught by Imam Al-Ghazali, namely balanced, beneficial, and non-excessive consumption. The conclusion of this study emphasizes that FOMO is a factor in impulse buying.